PHD finger proteins function in plant development and abiotic stress responses: an overview - Quan, Wenli; Chan, Zhulong; Wei, Piwei; Mao, Yahui; Bartels, Dorothea; Liu, Xun (Frontiers in Plant Science, 2023)
The plant homeodomain (PHD) finger with a conserved Cys4-His-Cys3 motif is a common zinc-binding domain, which is widely present in all eukaryotic genomes. The PHD finger is the "reader" domain of methylation marks in histone H3 and plays a role in the regulation of gene expression patterns. Numerous proteins containing the PHD finger have been found in plants. In this review, we summarize the functional studies on PHD finger proteins in plant growth and development, and responses to abiotic stresses in recent years. Some PHD finger proteins, such as VIN3, VILs, and Ehd3, are involved in the regulation of flowering time; while some PHD finger proteins participate in the pollen development, for example MS, TIP3 and MMD1.What's more, other PHD finger proteins regulate the plant tolerance to abiotic stresses, including Alfin1, ALs and AtSIZ1. These researches indicate that as an important transcription regulator family, most PHD finger proteins play critical roles in plant various biological events Research suggests that PHD finger proteins, as an essential transcription regulator family, play critical roles in various plant biological processes, which are is helpful for understanding the molecular mechanisms of novel PHD finger proteins to perform specific function.